The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

From kelp forests to turf reefs: Patterns, drivers, and impacts to functional diversity - Shane P. Farrell; Dara S. Yiu; Stuart K. Ryan; Rene D. Francolini; Courtney E. Stuart; Jonathan S. Lefcheck; Yasmina M. Shah Esmaeili; Douglas B. Rasher (Ecology, 2026)
Kelp forests are declining in many regions due to ocean warming, predator loss, and other anthropogenic stressors. In areas of rapid ocean warming, including the southern Gulf of Maine, these ecosystems have transitioned to a novel state dominated by low‐lying mats of turf algae. However, the pace, drivers, and ecological consequences of this transition remain unclear. Here, we used field surveys from 32 sites over 5 years (2018–2023) to reveal a continuation of kelp forest collapse and northward expansion of turf algae across Maine's coast. Next, we united data on benthic cover with key environmental variables in a structural equation model to show that turf algae were directly enhanced by higher ocean temperatures and decreased wave disturbance and indirectly enhanced by a warming‐induced loss of kelp cover. Lastly, we revealed the shift from kelp to turf yielded a seaweed assemblage dominated by traits associated with rapid growth, high surface area‐to‐volume ratios, and markedly reduced canopy height, indicating declines in habitat provisioning and carbon storage with kelp forest loss. Our findings highlight the accelerating impacts of climate change on temperate reef ecosystems and the vital services they provide. Further, we provide insights into a new state shift that is now occurring globally and underscore the need for urgent actions to mitigate further loss of foundational kelp forests.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Peatland use and peat soil land cover types in Ireland: Implications for the calculation of GHG emissions in the context of climate action - L. Gilet; W. Habib; E. Aitova; K.A. Byrne; C.A. Farrell; O. Fenton; R. Flynn; D. O’Leary; T.R. Morley; P. Tuohy; S. Regan; F. Renou-Wilson; et al. (Land Use Policy, 2025)

Fracture analysis of the lithium-bearing Cligga Head granite: Impacts on critical mineral mobilisation and fluid flow - Andrew J.M. Evans; Natalie J.C. Farrell; David A. Neave; Margaret E. Hartley; David Healy; John P. Waters; Tara R. McElhinney; Joshua J. Shea; Nico Bigaroni; Simon A. Hunt (Journal of Structural Geology, 2025)

On the equatorial dayside ionosphere of Saturn – In-situ observations give evidence for a dynamic and layered structure in disequilibrium - J.-E. Wahlund; A.I. Eriksson; M.W. Morooka; S. Buchert; M. Persson; E. Vigren; J. Dreyer; W.S. Kurth; J.H. Jr Waite; J.-P. Lebreton; W.M. Farrell; I. Müller-Wodarg (Icarus, 2025)

Temperature matters: Acute and latent toxicity of diluted bitumen to developing salmon is potentiated by a modest increase in water temperature - Derin M. Çalık; Feng Lin; Mackenzie Edgar; Anthony P. Farrell; Christopher J. Kennedy; Todd E. Gillis; Sarah L. Alderman (Aquatic Toxicology, 2025)

Review of APSIM's soil nitrogen modelling capability for agricultural systems analyses - Kirsten Verburg; Heather R. Pasley; Jody S. Biggs; Iris Vogeler; Enli Wang; Henrike Mielenz; Val O. Snow; Chris J. Smith; Chiara Pasut; Andrea D. Basche; Di He; Sotirios V. Archontoulis; et al. (Agricultural Systems, 2025)

Endurance Swimming Is Related to Summer Lake Survival of Rainbow Trout in a Warm Lake with Avian Piscivores - Christine E. Verhille; Anthony P. Farrell (Fishes, 2023)
Fitness of fish is assumed to be influenced by locomotion performance, but empirical evidence linking swimming capacity to survival in nature remains sparse. Poor triploid (3N) fish aerobic swimming performance in conjunction with production of sibling diploid (2N) and 3N populations of genetically identical origin to minimize variability among compared populations make 3N trout an informative system to test hypotheses about fitness consequences of fish locomotion. Here, we ask if reduced survival of 3N relative to 2N trout in natural ecosystems during periods of high temperature relate to a lower aerobic swimming capacity and aerobic scope of 3N compared with 2N conspecifics. Three-yearly cohorts of conspecific 2N and 3N hatchery-reared, yearling rainbow trout were ranked for swimming endurance, externally marked for their endurance quantile, and then stocked into two lakes as yearlings to quantify their survival in the wild over summer as a function of ploidy, temperature and endurance; all while tracking temperature and depth habitat utilization via telemetry. As expected, 3N swimming endurance was lower than that of 2N, but with considerable individual overlap. Aerobic swimming endurance, especially for 3N, was predictive of summer survival in a warm lake where piscivorous birds potentially exerted high predation pressure, resulting in low fish survival. This empirical evidence of a connection between swimming endurance and fitness provides support for long held assumptions of this relationship and could inform future sport fishing stocking industry practices to match fish strains to ideal habitats.

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

Stable carbon and nitrogen isotopes explain methylmercury concentrations in stream food webs of Lake George, New York (USA) - M. W. Swinton; P. K. Myer; M. F. Schaller; E. A. Pettitt; J. L. Farrell; S. A. Nierzwicki-Bauer (Ecotoxicology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Historical biogeography of smoothhound sharks (genus Mustelus ) of Southern Africa reveals multiple dispersal events from the Northern Hemisphere - Simo N. Maduna; Kelvin L. Hull; Edward D. Farrell; Jessica J. Boomer; Ana Veríssimo; Ilaria A. M. Marino; Carlotta Mazzoldi; Lorenzo Zane; Sabine P. Wintner; Mikhail V. Chesalin; Charlene da Silva; Chrysoula Gubili; et al. (Systematics and Biodiversity, 2020)

RGD-decorated cholesterol stabilized polyplexes for targeted siRNA delivery to glioblastoma cells - Bo Lou; Kate Connor; Kieron Sweeney; Ian S. Miller; Alice O’Farrell; Eduardo Ruiz-Hernandez; David M. Murray; Garry P. Duffy; Alan Wolfe; Enrico Mastrobattista; Annette T. Byrne; Wim E. Hennink (Drug Delivery and Translational Research, 2019)

Global Mammal Parasite Database version 2.0 - Patrick R. Stephens; Paula Pappalardo; Shan Huang; James E. Byers; Maxwell J. Farrell; Alyssa Gehman; Ria R. Ghai; Sarah E. Haas; Barbara Han; Andrew W. Park; John P. Schmidt; Sonia Altizer; et al. (Ecology, 2017)
Illuminating the ecological and evolutionary dynamics of parasites is one of the most pressing issues facing modern science, and is critical for basic science, the global economy, and human health. Extremely important to this effort are data on the disease‐causing organisms of wild animal hosts (including viruses, bacteria, protozoa, helminths, arthropods, and fungi). Here we present an updated version of the Global Mammal Parasite Database, a database of the parasites of wild ungulates (artiodactyls and perissodactyls), carnivores, and primates, and make it available for download as complete flat files. The updated database has more than 24,000 entries in the main data file alone, representing data from over 2700 literature sources. We include data on sampling method and sample sizes when reported, as well as both “reported” and “corrected” (i.e., standardized) binomials for each host and parasite species. Also included are current higher taxonomies and data on transmission modes used by the majority of species of parasites in the database. In the associated metadata we describe the methods used to identify sources and extract data from the primary literature, how entries were checked for errors, methods used to georeference entries, and how host and parasite taxonomies were standardized across the database. We also provide definitions of the data fields in each of the four files that users can download.

The macroecology of infectious diseases: a new perspective on global‐scale drivers of pathogen distributions and impacts - Patrick R. Stephens; Sonia Altizer; Katherine F. Smith; A. Alonso Aguirre; James H. Brown; Sarah A. Budischak; James E. Byers; Tad A. Dallas; T. Jonathan Davies; John M. Drake; Vanessa O. Ezenwa; Maxwell J. Farrell; et al. (Ecology Letters, 2016)
Identifying drivers of infectious disease patterns and impacts at the broadest scales of organisation is one of the most crucial challenges for modern science, yet answers to many fundamental questions remain elusive. These include what factors commonly facilitate transmission of pathogens to novel host species, what drives variation in immune investment among host species, and more generally what drives global patterns of parasite diversity and distribution? Here we consider how the perspectives and tools of macroecology, a field that investigates patterns and processes at broad spatial, temporal and taxonomic scales, are expanding scientific understanding of global infectious disease ecology. In particular, emerging approaches are providing new insights about scaling properties across all living taxa, and new strategies for mapping pathogen biodiversity and infection risk. Ultimately, macroecology is establishing a framework to more accurately predict global patterns of infectious disease distribution and emergence.

Seasonal migration of the starry smooth‐hound shark Mustelus asterias as revealed from tag‐recapture data of an angler‐led tagging programme - N. W. P. Brevé; H. V. Winter; H. M. J. Van Overzee; E. D. Farrell; P. A. Walker (Journal of Fish Biology, 2016)
The primary aim of this long‐term angler‐led tagging programme was to gain information about seasonal changes in distribution of the starry smooth‐hound shark Mustelus asterias , along the Dutch coast for management and conservation purposes. Between 2011 and 2014, M. asterias comprised 92·6% ( n = 2418) of the total elasmobranch catch ( n = 2612) by the licenced group of taggers within the Dutch Delta of which 2244 M. asterias were fin‐tagged with plastic rototags. Sex and total length ( L T ) composition inside the eastern tidal basin (Oosterschelde) were significantly different, i.e. more females and larger individuals, than outside indicating a pupping ground, which was confirmed by the capture of 30 newborn pups (≤32 cm). The distribution pattern of reported recaptured M. asterias (return‐rate 3·6%, n = 80) showed a circannual migration between summering in the southern North Sea and wintering in the English Channel and the Bay of Biscay, and suggests that M. asterias is philopatric. The Dutch angling season for M. asterias runs from approximately mid‐May to mid‐October when the water temperature is above 13° C. Recaptures of eight mature females, but no males in the Bay of Biscay, indicate partial spatial segregation by sex, where mature females migrate over larger distances than immature females and males. These observations, with the absence of recaptures in other known summering areas ( i.e. the Irish Sea and Bristol Channel), suggest that the southern North Sea is used by a separate population. Implications for management and recommendations to improve and expand the study approach are discussed.

Laboratory rearing of wild Arctic cod Boreogadus saida from egg to adulthood - D. Kent; H. E. Drost; J. Fisher; T. Oyama; A. P. Farrell (Journal of Fish Biology, 2016)
The techniques and protocols used to successfully capture, transport and breed Arctic cod Boreogadus saida , as well as to rear their larvae through to adulthood are summarized. Breeding B. saida will increase the opportunity to study this fish species, which is a critical part of the Arctic food web.

Upper thermal limits of the hearts of Arctic cod Boreogadus saida : adults compared with larvae - H. E. Drost; J. Fisher; F. Randall; D. Kent; E. C. Carmack; A. P. Farrell (Journal of Fish Biology, 2016)
Wild adult and reared larval Boreogadus saida were acclimated to 3·5° C before testing their cardiac response to acute warming. Heart rate transition temperatures during warming were similar for adult and larval hearts, except that the maximum temperature for heart rate was 3° C warmer for adults. Thus, in a rapidly warming Arctic Ocean, the upper temperature limit for larval rather than adult B. saida appears more likely to dictate the southern range of the species.

Oxygen uptake in Pacific salmon Oncorhynchus spp.: when ecology and physiology meet - E. J. Eliason; A. P. Farrell (Journal of Fish Biology, 2016)
Over the past several decades, a substantial amount of research has examined how cardiorespiratory physiology supports the diverse activities performed throughout the life cycle of Pacific salmon, genus Oncorhynchus . Pioneering experiments emphasized the importance of aerobic scope in setting the functional thermal tolerance for activity in fishes. Variation in routine metabolism can have important performance and fitness consequences as it is related to dominance, aggression, boldness, territoriality, growth rate, postprandial oxygen consumption, life history, season, time of day, availability of shelter and social interactions. Wild fishes must perform many activities simultaneously ( e.g . swim, obtain prey, avoid predators, compete, digest and reproduce) and oxygen delivery is allocated among competing organ systems according to the capacity of the heart to deliver blood. For example, salmonids that are simultaneously swimming and digesting trade‐off maximum swimming performance in order to support the oxygen demands of digestion. As adult Pacific salmonids cease feeding in the ocean prior to their home migration, endogenous energy reserves and cardiac capacity are primarily partitioned among the demands for swimming upriver, sexual maturation and spawning behaviours. Furthermore, the upriver spawning migration is under strong selection pressure, given that Pacific salmonids are semelparous (single opportunity to spawn). Consequently, these fishes optimize energy expenditures in a number of ways: strong homing, precise migration timing, choosing forward‐assist current paths and exploiting the boundary layer to avoid the strong currents in the middle of the river, using energetically efficient swimming speeds, and recovering rapidly from anaerobic swimming. Upon arrival at the spawning ground, remaining energy can be strategically allocated to the various spawning behaviours. Strong fidelity to natal streams has resulted in reproductively isolated populations that appear to be locally adapted physiologically to their specific environmental conditions. Populations with more challenging migrations have enhanced cardiorespiratory performance. Pacific salmonids are able to maintain aerobic scope across the broad range of temperatures encountered historically during their migration; however, climate change‐induced river warming has created lethal conditions for many populations, raising conservation concerns. Despite considerable research examining cardiorespiratory physiology in Pacific salmonids over the last 70 years, critical knowledge gaps are identified.

Environmental conditions and physiological state influence estuarine movements of homing sockeye salmon - S. Matthew Drenner; Scott G. Hinch; Eduardo G. Martins; Nathan B. Furey; Timothy D. Clark; Steven J. Cooke; David A. Patterson; David Robichaud; David W. Welch; Anthony P. Farrell; Richard E. Thomson (Fisheries Oceanography, 2015)
The reproductive migration of anadromous salmonids through estuarine waters is one of the most challenging stages of their life cycle, yet little is known about the environmental and physiological conditions that influence migratory behaviour. We captured, sampled tissues, tagged and released 365 sockeye salmon ( Oncorhynchus nerka ) homing through inner coastal waters towards the Fraser River, British Columbia, Canada. Biotelemetry was used to assess the behaviour of individual sockeye salmon approaching estuarine waters and at river entry, which were related to both fish physiological condition at release and to prevailing environmental conditions. Sockeye salmon tended to stay close to the shore, migrated during the day, and movements were related to tide. Sockeye salmon migration rate was linked to wind‐induced currents, salinity and an individual's physiological state, but these factors were specific to location and stock. We propose that wind‐induced currents exposed sockeye salmon entering the estuary to stronger olfactory cues associated with Fraser River water, which in turn resulted in faster migration rates presumably due to either an increased ability for olfactory navigation and/or advanced reproductive schedule through a neuroendocrine response to olfactory cues. However, once the migration had progressed further into more concentrated freshwater of the river plume, sockeye salmon presumably used wind‐induced currents to aid in movements towards the river, which may be associated with energy conservation. Results from this study improve our biological understanding of the movements of Fraser River sockeye salmon and are also broadly relevant to other anadromous salmonids homing in marine environments.

Upper thermal limits of cardiac function for Arctic cod Boreogadus saida , a key food web fish species in the Arctic Ocean - H. E. Drost; E. C. Carmack; A. P. Farrell (Journal of Fish Biology, 2014)
The objective of this study was to determine the upper thermal limits of Arctic cod Boreogadus saida by measuring the response of maximum heart rate ( f Hmax ) to acute warming. One set of fish were tested in a field laboratory in Cambridge Bay ( CB ), Nunavut (north of the Arctic Circle), and a second set were tested after air transport to and 6 month temperature acclimation at the Vancouver Aquarium ( VA ) laboratory. In both sets of tests, with B. saida acclimated to 0° C, f Hmax increased during acute warming up to temperatures considerably higher than the acclimation temperature and the near‐freezing Arctic temperatures in which they are routinely found. Indeed, f Hmax increased steadily between 0·5 and 5·5° C, with no significant difference between the CB and VA tests ( P > 0·05) and with an overall mean ± s.e. Q 10 of 2·4 ± 0·5. The first Arrhenius breakpoint temperature ( T AB ) for f Hmax was also statistically indistinguishable for the two sets of tests (mean ± s.e. 3·2 ± 0·3 and 3·6 ± 0·3° C), suggesting that the temperature optimum for B. saida could be reliably measured after live transport to a more southerly laboratory location. Continued warming above 5·5° C revealed a large variability among individuals in the upper thermal limits that triggered cardiac arrhythmia ( T arr ), ranging from 10·2 to 15·2° C with mean ± s.e. 12·4 ± 0·4° C ( n = 11) for the field study. A difference did exist between the CB and VA breakpoint temperatures when the Q 10 value decreased below 2 (the Q 10 breakpoint temperature; T QB ) at 8·0 and 5·5° C, respectively. These results suggest that factors, other than thermal tolerance and associated cardiac performance, may influence the realized distribution of B. saida within the Arctic Circle.

Facing warm temperatures during migration: cardiac mRNA responses of two adult Oncorhynchus nerka populations to warming and swimming challenges - K. Anttila; E. J. Eliason; K. H. Kaukinen; K. M. Miller; A. P. Farrell (Journal of Fish Biology, 2014)
The main findings of the current study were that exposing adult sockeye salmon Onchorhynchus nerka to a warm temperature that they regularly encounter during their river migration induced a heat shock response at an mRNA level, and this response was exacerbated with forced swimming. Similar to the heat shock response, increased immune defence‐related responses were also observed after warm temperature treatment and with a swimming challenge in two different populations (Chilko and Nechako), but with some important differences. Microarray analyses revealed that 347 genes were differentially expressed between the cold (12–13° C) and warm (18–19° C) treated fish, with stress response ( GO :0006950) and response to fungus ( GO :0009620) elevated with warm treatment, while expression for genes involved in oxidative phosphorylation ( GO :0006119) and electron transport chain ( GO :0022900) elevated for cold‐treated fish. Analysis of single genes with real‐time quantitative PCR revealed that temperature had the most significant effect on mRNA expression levels, with swimming and population having secondary influences. Warm temperature treatment for the Chilko population induced expression of heat shock protein ( hsp ) 90α , hsp90β and hsp30 as well as interferon‐inducible protein . The Nechako population, which is known to have a narrower thermal tolerance window than the Chilko population, showed even more pronounced stress responses to the warm treatment and there was significant interaction between population and temperature treatment for hsp90β expression. Moreover, significant interactions were noted between temperature treatment and swimming challenge for hsp90α and hsp30 , and while swimming challenge alone increased expression of these hsp s, the expression levels were significantly elevated in warm‐treated fish swum to exhaustion. In conclusion, it seems that adult O. nerka currently encounter conditions that induce several cellular defence mechanisms during their once‐in‐the‐lifetime migration. As river temperatures continue to increase, it remains to be seen whether or not these cellular defences provide sufficient protection for all O. nerka populations.

Multivariate analysis of MLH1 c.1664T>C (p.Leu555Pro) mismatch repair gene variant demonstrates its pathogenicity - M. P. Farrell; D. J. Hughes; M. Drost; A. J. Wallace; R. J. Cummins; T. A. Fletcher; M. A. Meany; E. W. Kay; N. de Wind; D. G. Power; E. J. Andrews; A. J. Green; et al. (Familial Cancer, 2013)

Low cardiac and aerobic scope in a coastal population of sockeye salmon Oncorhynchus nerka with a short upriver migration - E. J. Eliason; S. M. Wilson; A. P. Farrell; S. J. Cooke; S. G. Hinch (Journal of Fish Biology, 2013)
This study showed that a coastal population (Harrison) of Fraser River sockeye salmon Oncorhynchus nerka had a lower aerobic and cardiac scope compared with interior populations with more challenging upriver spawning migrations, providing additional support to the idea that Fraser River O. nerka populations have adapted physiologically to their local migratory environment.

Commitment to the environment and student support for “green” campus initiatives - Anthony E. Coy; Allison K. Farrell; Katharine P. Gilson; Jody L. Davis; Benjamin Le (Journal of Environmental Studies and Sciences, 2013)

Clinical correlation and molecular evaluation confirm that the MLH1 p.Arg182Gly (c.544A>G) mutation is pathogenic and causes Lynch syndrome - Michael P. Farrell; David J. Hughes; Ian R. Berry; David J. Gallagher; Emily A. Glogowski; Stewart J. Payne; Michael J. Kennedy; Róisín M. Clarke; Susan A. White; Cian B. Muldoon; Fiona Macdonald; Pauline Rehal; et al. (Familial Cancer, 2012)

Balancing selection on MHC class I in wild brown trout Salmo trutta - B. O’Farrell; C. Dennis; J. A. Benzie; P. McGinnity; J. Carlsson; E. de Eyto; J. P. Coughlan; F. Igoe; R. Meehan; T. F. Cross (Journal of Fish Biology, 2012)
Evidence is reported for balancing selection acting on variation at major histocompatibility complex (MHC) in wild populations of brown trout Salmo trutta . First, variation at an MHC class I ( satr‐uba )–linked microsatellite locus ( mhc1 ) is retained in small S . trutta populations isolated above waterfalls although variation is lost at neutral microsatellite markers. Second, populations across several catchments are less differentiated at mhc1 than at neutral markers, as predicted by theory. The population structure of these fish was also elucidated.

Simultaneous biologging of heart rate and acceleration, and their relationships with energy expenditure in free-swimming sockeye salmon (Oncorhynchus nerka) - Timothy Darren Clark; E. Sandblom; S. G. Hinch; D. A. Patterson; P. B. Frappell; A. P. Farrell (Journal of Comparative Physiology B, 2010)

Tensile Strain as a Regulator of Mesenchymal Stem Cell Osteogenesis - E. M. Kearney; E. Farrell; P. J. Prendergast; V. A. Campbell (Annals of Biomedical Engineering, 2010)

Calibration of a hand‐held haemoglobin analyser for use on fish blood - T. D. Clark; E. J. Eliason; E. Sandblom; S. G. Hinch; A. P. Farrell (Journal of Fish Biology, 2008)
The HemoCue haemoglobin analyser consistently overestimated haemoglobin concentration ([Hb]) in the blood of all fish species (sockeye salmon Oncorhynchus nerka , Chinook salmon Oncorhynchus tshawytscha , Pacific bluefin tuna Thunnus orientalis and chub mackerel Scomber japonicus ) by 22–50% (9·9–36·0 g l −1 ) over a [Hb] range of 20–160 g l −1 . The systematic nature of the overestimation, however, allowed the formulation of an accurate calibration equation that can be used to correct values of [Hb] measured by the HemoCue in field studies.

Effect of planting stocktype and cultivation treatment on the establishment of Norway spruce on cutaway peatlands - Florence Renou-Wilson; Michael Keane; E. P. Farrell (New Forests, 2008)

Early performance of native birch (Betula spp.) planted on cutaway peatlands: influence of species, stock types and seedlings size - Florence Renou; Úna Scallan; Michael Keane; E. P. Farrell (European Journal of Forest Research, 2007)

Validation of the hepatic portal vein cannulation technique using Atlantic salmon Salmo salar L. - E. J. Eliason; A. Kiessling; A. Karlsson; B. Djordjevic; A. P. Farrell (Journal of Fish Biology, 2007)
This study assessed the hepatic portal vein cannulation technique and surgical recovery in Atlantic salmon Salmo salar. Haematocrit levels were maintained and blood variables, including cortisol, returned to baseline levels within 1–3 days post‐surgery, indicating that this technique is a viable, useful method to study the digestive physiology of fishes.

Comparison of results from several AOGCMs for global and regional sea-level change 1900-2100 - J. M. Gregory; J. A. Church; G. J. Boer; K. W. Dixon; G. M. Flato; D. R. Jackett; J. A. Lowe; S. P. O'Farrell; E. Roeckner; G. L. Russell; R. J. Stouffer; M. Winton (Climate Dynamics, 2001)

Sulfur K-edge XANES study of local electronic structure in ternary monosulfide solid solution [(Fe, Co, Ni) 0.923 S] - S. P. Farrell; M. E. Fleet (Physics and Chemistry of Minerals, 2001)

A Study of the Lethal and Sublethal Toxicity of Polyphase P-100, an Antisapstain Fungicide Containing 3-Iodo-2-Propynyl Butyl Carbamate (IPBC), on Fish and Aquatic Invertebrates - A. P. Farrell; E. Stockner; C. J. Kennedy (Archives of Environmental Contamination and Toxicology, 2000)

A Study of the Lethal and Sublethal Toxicity of Polyphase P-100, an Antisapstain Fungicide Containing 3-Iodo-2-Propynyl Butyl Carbamate (IPBC), on Fish and Aquatic Invertebrates - A. P. Farrell; E. Stockner; C. J. Kennedy (Archives of Environmental Contamination and Toxicology, 1998)

Influence of earthworms on soil properties and grass production in reclaimed cutover peat - K. E. Boyle; J. P. Curry; E. P. Farrell (Biology and Fertility of Soils, 1997)

Molecular and biological characterization of new strains of murine cytomegalovirus isolated from wild mice - T. W. M. Booth; A. A. Scalzo; C. Carrello; P. A. Lyons; Helen E. Farrell; G. R. Singleton; G. R. Shellam (Archives of Virology, 1993)